Frontiers in combining immune checkpoint inhibitors for advanced urothelial cancer management - Rebhan, Katharina; Laukhtina, Ekaterina; Shariat, Shahrokh F; Gust, Kilian M (Current opinion in urology, 2020)
PURPOSE OF REVIEW: This review provides an overview of currently ongoing clinical trials evaluating the combination of immune checkpoint inhibitors (CPI) with other therapies in locally advanced or metastatic urothelial cancer and the rationale for this combination approach. We discuss the preliminary results from early data presented at recent meetings regarding the efficacy and safety of novel combination therapies including a CPI for metastatic urothelial cancer. RECENT FINDINGS: CPI emerged as novel first-line or second-line treatment options in advanced and metastatic urothelial cancer (mUC). Although the response rates and their sustainability are promising, it is far from a home run. Combination therapies have already shown improved efficacy in several other tumor entities. SUMMARY: Numerous clinical trials currently investigate combinations of CPI with other CPI, previously established systemic chemotherapy, targeted therapies, vaccines, or accompanied with radiotherapy. Preliminary data shows promising results. These results suggest that targeting pathways of immune response combined with established or novel oncological therapies may lead to a synergistic antitumor effect.
Keywords: klinické zkoušky jako téma; inhibitory kontrolních bodů; karcinom z přechodných buněk; Clinical Trials as Topic; Combined Modality Therapy; urologické nádory; Urologic Neoplasms; Carcinoma, Transitional Cell; protinádorové látky imunologicky aktivní; Humans; Immune Checkpoint Inhibitors; Antineoplastic Agents, Immunological; kombinovaná terapie; lidé